Boosting Student Motivation and Science Understanding in the GCE 'O' Level Combined Science through AT-TPACK Framework - Yong Chin Chen; Sallimah Binti Hj Mohd Salleh; Iwan Wicaksono (Jurnal Inovasi Pendidikan IPA, 2026)
The particular study examined the impact of science boost camp interventions, utilizing the activity theory and TPACK (AT-TPACK) framework, on the achievements of sixty-eight Year 11 combined science students following the new Cambridge 5129 syllabus, including Paper 3 components, in Muara, Brunei. These students, learning combined science in English as their second language for three years, scored below 60% in their SPE Year 8 science exams, placing them in the Applied Secondary Education Programme (one class of 20 students) and the Special Applied Program (three classes of 48 students). The study used a pre-test-post-test and delayed post-test experimental design to evaluate the effectiveness of the proposed three-phase AT-TPACK model. The primary goal was to enhance students' combined science achievement and reduce the number of students receiving ungraded (below 30%) grades in the GCE O-Level examinations. After the mock exams, the sixty-eight students were randomly assigned to fourteen intervention groups based on their academic performance. Each group, led by a higher achiever (HA) student, participated in science interventions. This study examines the impact of science boost camp interventions, utilizing the activity theory and TPACK (AT-TPACK) framework, on the achievements of sixty-eight Year 11 combined science students following the new Cambridge 5129 syllabus, including Paper 3 components, in Muara, Brunei. The students were selected through purposive sampling, involving 20 students from Year 11A (General Applied Program) and 48 from Year 11B to 11C2 (Special Applied Program). These students, learning combined science in English as their second language for three years, scored below 60% in their SPE Year 8 science exams, placing them in the Applied Secondary Education Programme. The aspects measured in this study included students' motivation, conceptual understanding, and collaborative learning performance. The results revealed significant improvement in achievement scores postintervention and a reduction in ungraded grades, with thematic analysis indicating sustained retention of scientific concepts even after the 20-week intervention period. Students' GCE O-level exam performance improved, with the school achieving its 2023 target for combined science, increasing from 19% to 35%, placing the school in the second-highest rank in the country. These findings highlight the potential of targeted interventions to address challenges in combined science education, offering insights for educators seeking to enhance student outcomes in similar contexts.